2022
DOI: 10.1002/vms3.1008
|View full text |Cite
|
Sign up to set email alerts
|

Manganese–methionine chelate improves antioxidant activity, immune system and egg manganese enrichment in the aged laying hens

Abstract: Background It has been reported that supplementation of manganese (Mn) could alleviate the negative effects of age on egg quality in laying hens. However, limited information is available on compensatory ways in order to reduce the adverse effects of hen age on health and Mn deposition in the body. Objectives The objectives were to investigate the effect of organic and inorganic sources of Mn on antioxidant activity, immune system, liver enzymes, shell quality and Mn de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…It is unclear why the treatment diets produced significant effects on egg weight only during week 10 of the experiment, although this may be attributed to the age of the hens used and corresponding changes in mineral absorption [12]. Khoshbin, Vakili, and Tahmasbi [14] found that feeding late-lay hens a 50/50 or 25/75 ratio of MnSO 4 and AAC Mn increased hen day egg production and egg mass compared to feeding 100% inorganic Mn. Overall, the results of this experiment agree with several previous studies in late-phase laying hens in which feeding AAC or sulfated minerals did not affect egg production [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear why the treatment diets produced significant effects on egg weight only during week 10 of the experiment, although this may be attributed to the age of the hens used and corresponding changes in mineral absorption [12]. Khoshbin, Vakili, and Tahmasbi [14] found that feeding late-lay hens a 50/50 or 25/75 ratio of MnSO 4 and AAC Mn increased hen day egg production and egg mass compared to feeding 100% inorganic Mn. Overall, the results of this experiment agree with several previous studies in late-phase laying hens in which feeding AAC or sulfated minerals did not affect egg production [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The increased bioavailability of AAC Mn may be enough to counter any impairments in intestinal absorption. Feeding AAC minerals to late-lay hens may even improve intestinal function, including absorption and utilization of said minerals [15], and antioxidative capabilities [14]. Although these parameters were not included in the design of this experiment, they may account for differences in mineral retention.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of eggs of laying hens is an important indicator of poultry production due to the fact that they are considered as a good and economically justified source of high-grade protein in the diet of the human population, especially with limited financial resources [36,37].…”
Section: Performance Indicators and Feed Efficiency Of Brown Nick Cro...mentioning
confidence: 99%
“…The shift in research topics from growth and performance in the 1990s to meat quality and antioxidant status in 2010s suggests that increasing numbers of researchers were gradually becoming involved in studies addressing the quality of meat and antioxidant status in farm animals. Several studies have been performed demonstrating the protective and beneficial effects of CTM on animal production, health and, eggshell quality [95], enriched egg content [96] and other metabolic variables in animal nutrition, such as acid-base [30] and antioxidant status [30,96,97]. Therefore, this intellectual structure and network analysis provides insight into the evolution and emerging trends in chelate research and allows researchers to identify key research areas and potential gaps in current research.…”
Section: The Intellectual Structure and Network Of The Chelate Fieldmentioning
confidence: 99%